Morphometric and elemental microanalytical studies of human lung in health and disease. Issue 1 (January 1985) - Siegesmund, K A; Funahashi, A; Yorde, D E
Abstract : Current methods for determining the fibrogenicity of substances are based on relatively long term exposures of animals to the substance and the evaluation of morphological changes occurring in the lung. The use of inhalation chambers, which produce a more physiological environment, suffer from the need for particularly long exposure times (1-3 years). The present study describes a technique using scanning electron microscopy, energy dispersive analysis, and a digitiser pad with a computer to evaluate the fibrogenicity of silica in cases of known exposure. Scanning electron micrographs taken from silicotic lungs were evaluated for the degree of thickening (fibrosis) and the same areas were analysed for silicon content. Correlations between silicon content and septal thickening were shown to be significant (p less than 0.0001). The study also describes the concentrations of elements found in normal lungs. The technique for establishing correlation curves between elemental concentrations and septal thickening could be of value in determining the fibrogenicity of pure substances after short exposures in an environmental chamber.